Integrated nutrient management - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
Soil fertilization is a fundamental practice for increasing crop yields and ensuring sustainable agricultural production. As shown in Figure 1, the use of fertilizers has been growing over the years, reflecting the importance of fertilization in all agricultural systems. However, several environmental issues and potential health risks arise from incorrect approaches to fertilization in both high-income and low-income countries.